The “brain-gut” mechanism of postherpetic neuralgia: a mini-review - Zhang, Peijun; Zhang, Cuomaoji; Zheng, Bixin; Liu, Yuntao; Zhang, Dingkun; Xiao, Hong (Frontiers in Neurology, 2025)
Postherpetic neuralgia (PHN), a representative type of neuropathic pain, has attracted much research on its diagnosis and therapy at the molecular level. Interestingly, this study based on the brain-gut axis provided a novel point of view to interpret the mechanism of PHN. Past neuroanatomical and neuroimaging studies of pain suggest that the prefrontal cortex, anterior cingulate cortex, amygdala, and other regions of the brain may play crucial roles in the descending inhibition of PHN. Dominant bacterial species in patients with PHN, such as Lactobacillus, generate short-chain fatty acids, including butyrate. Evidence indicates that disturbance of some metabolites (such as butyrate) is closely related to the development of hyperalgesia. In addition, tryptophan and 5-HT in the intestinal tract act as neurotransmitters that regulate the descending transmission of neuropathic pain signals. Concurrently, the enteric nervous system establishes close connections with the central nervous system through the vagus nerve and other pathways. This review aims to investigate and elucidate the molecular mechanisms associated with PHN, focusing on the interplay among PHN, the gut microbiota, and relevant metabolites while scrutinizing its pathogenesis.